Independent prognostic significance of tumor budding and poorly differentiated clusters in Brazilian patients with stage II colorectal cancer - Monise Tadin Reis; Marcus Matsushita; Wellington Santos; Gustavo Noriz Berardinelli; Valiana Teodoro; Mariana Bisarro dos Reis; Denise Peixoto Guimarães; Rui Manuel Reis (Surgical and Experimental Pathology)
Abstract Background Colorectal cancer (CRC) is the third most commonly diagnosed and the second most fatal cancer worldwide. Tumor budding (TB) and poorly differentiated clusters (PDC) are morphological features with significant prognostic value that may aid therapeutic decisions, particularly in stage II patients. The present study aimed to determine the prognostic role of TB and PDC in a Brazilian population. Methods TB and PDC were evaluated on H&E slides according to International Tumor Budding Consensus Conference (ITBCC) guidelines in 257 stage II primary colorectal cancer patients, characterized for microsatellite instability (MSI) and BRAF V600E mutation. Clinicopathological, molecular associations, five and 10-year disease-specific survival (DSS), and disease-free survival (DFS) were evaluated. Results High TB and/or high PDC were associated with clinicopathological features of aggressiveness, such as angiolymphatic invasion, recurrence or metastasis, perineural invasion, BRAF V600E mutation, and MSI-H tumors. Patients with high TB and high PDC have lower DSS and DFS compared with low TB and low PDC, and the survival was even lower when patients did not receive adjuvant chemotherapy. On a multivariate Cox Regression analysis, patients with high TB had a higher risk of recurrence or metastasis (HR = 4.213), and patients with high PDC had a significantly higher risk of death by cancer (HR = 4.181). Conclusions TB and PDC are independent prognostic factors in stage II Brazilian patients with CRC and must be considered when making therapeutic decisions.